Detecting incipient radial deformations of power transformer windings using polar plot and digital image processing - Abu-Siada, Ahmed; Aljohani, O. (Institution of Engineering and Technology, 2018)
One of the main drawbacks of the frequency response analysis (FRA) technique that is widely accepted as the most reliable tool to detect transformer internal mechanical deformations is the inconsistent interpretation of the measured signature because of its reliance on personal expertise more than standard codes. Moreover, conventional FRA signature has a very low accuracy in detecting incipient and low mechanical fault levels. In order to avoid inconsistent interpretation for the transformer FRA signatures and improve its accuracy to detect minor fault levels, a reliable automated technique has become essential. This study investigates the feasibility of utilising FRA polar plot to detect minor radial deformation levels within two, three-phase power transformers of different ratings and winding configurations simulated using three-dimensional finite-element analysis software. Simulation results are validated through experimental measurements. Results of this study are also compared with the results obtained for other types of transformer winding deformations that are published in the literature in order to identify unique impact for each fault type on the proposed method. Findings reveal the superiority of the proposed approach over existing conventional technique in terms of accurate identification and quantification for minor transformer winding deformations.